Conserved scalar and progress variable for internal combustion engine simulation with chemical kinetics - Tsukasa HORI (Nihon Kikai Gakkai ronbunshu, 2018)
The conserved scalar and progress variable have been modified and proposed for spray and engine combustion simulation with chemical kinetics. The global equivalence ratio (GER) and progress equivalence ratio (PER) were proposed as the conserved scalar and progress variable in multi-zone model for engine simulations with chemical kinetics (Babajimopoulos et al., 2005). The combination of GER and PER work in lean mixture without EGR gas. But these would not work under rich mixture or EGR gas conditions. Thus, the modified GER is proposed to apply the EGR gas conditions where CO2 and H2O mix in air. Furthermore, the progress variable based on the chemical energy also proposed with modified GER. The zero-dimensional combustion simulations are done under constant pressure and adiabatic conditions to validate the proposed indexes. The reaction mechanism is the detailed chemistry of n-dodecane. That consists of 1,255 chemical species and 3,075 reactions. The results show that the conventional GER works in any mixture as conserved scalar and is good agreement with equivalence ratio under the ambient gas of air. But, the conventional GER overestimates equivalence ratio in lean mixture and underestimates equivalence ratio in rich mixtures. The modified GER is good agreement with equivalence ratio under the ambient gas of air and EGR gas including CO2 and H2O, regardless of lean and rich mixtures. The results also indicate that the PER works in lean mixtures. But that do not work in stoichiometric and rich mixture. The progress variable based on the mass fraction of some chemical species (Van Oijen and De Goey, 2010) works in any mixture, but the that can not compare the reaction progress between different GER conditions. The proposed progress variable works in any mixture and compares the reaction progress at different GER conditions quantitatively.